The only mathematical model representation i2c3s systems with different levels of integration and rozpodilenosti - Павлова, С.В. (Proceedings of National Aviation University, 2008)
So-called "frame" modeling architectural representation of processes in the I2C3S-systems is developed. It allows on uniform structural bases to investigate and synthesize effective systems I2C3S, uniting two concepts − the concept of automatic control theory ACS-View and the concept of computer and telecommunication sciences CS&T-View.